2017
DOI: 10.1097/md.0000000000006423
|View full text |Cite|
|
Sign up to set email alerts
|

Nonspecific ST-T changes associated with unsatisfactory blood pressure control among adults with hypertension in China

Abstract: Nonspecific ST-segment and T-wave (ST-T) changes represent one of the most prevalent electrocardiographic abnormalities in hypertensive patients. However, a limited number of studies have investigated the association between nonspecific ST-T changes and unsatisfactory blood pressure (BP) control in adults with hypertension.The study population comprised 15,038 hypertensive patients, who were selected from 20,702 participants in the China Stroke Primary Prevention Trial. The subjects were examined with electroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The prevalence of NST abnormalities was higher in females (4.5% vs 2.3% in males; P <0.001) among healthy volunteers (Hingorani et al, 2012), and similar findings were also observed in an Australian Busselton study (Cullen et al, 1982) and the Michigan study (Ostrander Jr. et al, 1965). One study proposed that NST changes were associated with a remarkably higher incidence rate of unsatisfactory blood pressure control in hypertension patients, especially among diabetic patients (Bao et al, 2017). Kumar et al also concluded that patients with high blood pressure tended to have NST changes (Kumar et al, 2008).…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence of NST abnormalities was higher in females (4.5% vs 2.3% in males; P <0.001) among healthy volunteers (Hingorani et al, 2012), and similar findings were also observed in an Australian Busselton study (Cullen et al, 1982) and the Michigan study (Ostrander Jr. et al, 1965). One study proposed that NST changes were associated with a remarkably higher incidence rate of unsatisfactory blood pressure control in hypertension patients, especially among diabetic patients (Bao et al, 2017). Kumar et al also concluded that patients with high blood pressure tended to have NST changes (Kumar et al, 2008).…”
Section: Discussionmentioning
confidence: 56%
“…CVD can kill patients with CKD more often and more prematurely. The CVD spectrum in CKD and ESRD includes ischemic attributed to displaced transition of QRS complex, 3) Absent Q waves in leads I, V5 and V6 or a narrow Q wave in the absence of myocardial pathology in the lead aVL, 4) R peak time greater than 60 ms in leads V5and V6 but normal in leads V1, V2 and V3, when small initial R waves can be discerned in the above leads, 5) ST and T waves opposite in direction to QRS, 6) Positive T wave in leads with upright QRS, 7) Depressed ST segment and/or negative T wave in leads with negative QRS [ Inverted T wave deeper than  mm [] Non-specific ST-T changes 1) No ST-T depression ≥ 0.5 mm but ST-segment down-sloping and ST-segment or T-wave nadir at least 0.5 mm below the P-R baseline in any of leads I, II, aVL, or V2 to V6 2) ST-J depression ≥1.0 mm and ST-segment up-sloping or U-shaped in any of leads I, II, aVL, or V1 to V6 3) T-wave amplitude zero (flat), negative, or diphasic (negative-positive type only) with <1.0 mm negative phase in leads I, II, aVL, or V3 to V6 when R-wave amplitude is ≥ 5.0 mm, 4) T-wave amplitude positive and T-to R-wave amplitude ratio of <1:20 in any of leads I, II, aVL, or V3 to V6 when R wave amplitude in the corresponding leads was ≥10.0 mm [46] Pathologic Q wave Any Q wave with more than  ms width or a depth more than one-third of the adjacent R wave in more than two adjacent leads [ heart disease, congestive heart failure, arrhythmias and peripheral vascular disease. Initially, it was estimated that this only occurred in the ESRD population which was 20-30 times more likely to die from CVD compared to the general population.…”
Section: Discussionmentioning
confidence: 99%
“…T wave abnormalities in hypertensive individuals have reportedly varied widely, from nonspecific T wave abnormality to strain T wave abnormality is a marker of LVH and it portends poor prognosis in hypertensive patients. 37,38 The diagnostic yield of ECG in the youngest age group was below 10% for most ECG abnormalities with the notable exceptions of LVH (14.5%), abnormal rhythm (18.9%), rate (17.3%) and axis deviation (15%). This may be attributable to shorter duration of hypertension and lower prevalence of hypertensive heart disease in this group.…”
Section: Dovepressmentioning
confidence: 99%